The amino acid transporter SLC6A14 in cancer and its potential use in chemotherapy - Yangzom D. Bhutia; Ellappan Babu; Puttur D. Prasad; Vadivel Ganapathy (Elsevier, 2014)
Tumor cells have an increased demand for glucose and amino acids to support their rapid growth, and also exhibit alterations in biochemical pathways that metabolize these nutrients. Transport across the plasma membrane is essential to feed glucose and amino acids into these tumor cell-selective metabolic pathways. Transfer of amino acids across biological membranes occurs via a multitude of transporters; tumor cells must upregulate one or more of these transporters to satisfy their increased demand for amino acids. Among the amino acid transporters, SLC6A14 stands out with specific functional features uniquely suited for the biological needs of the tumor cells. This transporter is indeed upregulated in tumors of epithelial origin, including colon cancer, cervical cancer, breast cancer, and pancreatic cancer. Since normal cells express this transporter only at low levels, blockade of this transporter should lead to amino acid starvation selectively in tumor cells, thus having little effect on normal cells. This offers a novel, yet logical, strategy for the treatment of cancers that are associated with upregulation of SLC6A14. In addition, a variety of amino acid-based prodrugs are recognized as substrates by SLC6A14, thus raising the possibility that anticancer drugs can be delivered into tumor cells selectively via this transporter in the form of amino acid prodrugs. This strategy allows exposure of SLC6A14-positive tumor cells to chemotherapy with minimal off-target effects. In conclusion, the amino acid transporter SLC6A14 holds great potential not only as a direct drug target for cancer therapy but also for tumor cell-selective delivery of anticancer drugs.